The CASC15 long intergenic non-coding RNA locus is involved in melanoma progression and phenotype-switching - Lessard, Laurent (J Invest Dermatol, 2015)
In recent years, considerable advances have been made in the characterization of protein-coding alterations involved in the pathogenesis of melanoma. However, despite their growing implication in cancer, little is known about the role of long non-coding RNAs in melanoma progression. We hypothesized that copy number alterations of intergenic non-protein coding domains could help identify long intergenic non-coding RNAs (lincRNAs) associated with metastatic cutaneous melanoma. Among several candidates, our approach uncovered the chromosome 6p22.3 CASC15 lincRNA locus as a frequently gained genomic segment in metastatic melanoma tumors and cell lines. The locus was actively transcribed in metastatic melanoma cells, and up-regulation of CASC15 expression was associated with metastatic progression to brain metastasis in a mouse xenograft model. In clinical specimens, CASC15 levels increased during melanoma progression and were independent predictors of disease recurrence in a cohort of 141 patients with AJCC stage III lymph node metastasis. Moreover, siRNA knockdown experiments revealed that CASC15 regulates melanoma cell phenotype switching between proliferative and invasive states. Accordingly, CASC15 levels correlated with known gene signatures corresponding to melanoma proliferative and invasive phenotypes. These findings support a key role for CASC15 in metastatic melanoma.